2017
DOI: 10.1039/c7cc06086f
|View full text |Cite
|
Sign up to set email alerts
|

Topotactic transition of α-Co(OH)2to β-Co(OH)2anchored on CoO nanoparticles during electrochemical water oxidation: synergistic electrocatalytic effects

Abstract: Herein, we report a single step, anionic surfactant-assisted, low temperature-hydrothermal synthetic strategy of CoO nanoparticles anchored on β-Co(OH) nanosheets which show a low overpotential (295 mV @ 10 mA cm) for the oxygen evolution reaction (OER). They also demonstrate much better kinetic parameters compared to the state-of-the-art RuO. Interestingly, under the OER operational conditions (in alkaline medium), the topotactic transformation of α-Co(OH) to a stable Brucite-like β-Co(OH) phase leads to a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Both the samples show the main characteristic diffraction peaks at 11.2°, 22.4°, 33.9°, 38.2°and 45.5°, which are well assigned to (003), (006), (012), (015) and (018) reflections of the hydrotalcite-like phase compounds that consist of positively charged Co(OH) 2-x layers and charge balancing anions (JCPDS 53-1185). [20] Taking the green color into consideration (Figure 1b), the product prepared in CoCl 2 -HMT system can be rationally identified as α-Co(OH) 2 layered double hydroxide (LDH). [21] Therefore, the yellow product ( Then SEM and TEM characterizations were performed to analyze the microstructure and morphology of α-Co(OH) 2 and α-Co 0.9 Fe 0.1 (OH) x .…”
Section: Resultsmentioning
confidence: 99%
“…Both the samples show the main characteristic diffraction peaks at 11.2°, 22.4°, 33.9°, 38.2°and 45.5°, which are well assigned to (003), (006), (012), (015) and (018) reflections of the hydrotalcite-like phase compounds that consist of positively charged Co(OH) 2-x layers and charge balancing anions (JCPDS 53-1185). [20] Taking the green color into consideration (Figure 1b), the product prepared in CoCl 2 -HMT system can be rationally identified as α-Co(OH) 2 layered double hydroxide (LDH). [21] Therefore, the yellow product ( Then SEM and TEM characterizations were performed to analyze the microstructure and morphology of α-Co(OH) 2 and α-Co 0.9 Fe 0.1 (OH) x .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, further activity improvements have severely hindered by the poor intrinsic activity for the oxides, and limited activity sites for the LDHs . It is noteworthy that, numbers of recent studies have demonstrated that nanostructured composite catalysts usually exhibit exceptional electrocatalytic activities superior to their single‐component counterparts, primarily because of the strong chemical couplings between both components . Engineering the interfacial atoms or molecular of hybrid catalysts would trigger electronic or chemical modification in close proximity at the interfacial bonding, which in turn, induces synergistic effect to substantially enhance intrinsic electrocatalytic activities .…”
mentioning
confidence: 99%
“…All curves exhibit characteristic peaks at 11.2°, 22.4°, 33.9°, 38.2°, and 45.5°, which can be indexed to the (0 0 3), (0 0 6), (0 1 2), (0 1 5), and (0 1 8) reflections of the hydrotalcite‐like phase (JCPDS 53‐1185) . Taking the green color of the product prepared in the CoCl 2 /HMT system into consideration, this product can be rationally identified as α‐Co(OH) 2 . Also, the small peak of α‐Co(OH) 2 at 19.1° is assigned to the β‐Co(OH) 2 phase, as the α‐phase is metastable and partly transforms to the β‐form during the synthesis or upon storage in alkaline media .…”
Section: Resultsmentioning
confidence: 99%
“…[14] Taking the green color of the product prepared in the CoCl 2 /HMT system into consideration, this product can be rationally identified as a-Co(OH) 2 . [15] Also, the small peak of a-Co(OH) 2 at 19.18 is assigned to the b-Co(OH) 2 phase, as the a-phase is metastable and partly transforms to the b-form during the synthesis or upon storageinalkaline media. [16] Therefore, these products prepared in the CoCl 2 /FeCl 2 /HMT system can be assigned as a-Co 1Àm Fe m (OH) x as the incorporation of Fe does not change the crystal phase.…”
Section: Resultsmentioning
confidence: 99%